Modelling clearance sales shopping behaviour. (4th August 2010) - Hemalatha, M.; Sivakumar, V.J.; Narayanan, A.G.V.
This paper presents a structural equation model for understanding the clearance sales shopping behaviour. The study examines the impact of clearance sales store attributes on store satisfaction, the impact of store satisfaction on store loyalty and the impact of store loyalty on store equity. A total of 664 shoppers were surveyed during clearance sales in three different Indian cities. The structural equation model confirms that higher level of clearance sales store attributes will lead to higher store satisfaction, higher level of store satisfaction will lead to higher store loyalty and higher level of store loyalty will lead to higher store equity. The findings from the study proved that the impact of store loyalty on store equity is higher than the impact of store satisfaction on store loyalty and the impact of store attributes on store satisfaction.